UTAUT and UTAUT 2: A Review and Agenda for Future Research - Andreas Chang (The Winners, 2012)
This study reviews the most recent literature on UTAUT (Unified Theory of Acceptance, and Use of Technology) and UTAUT 2(Unified Theory of Acceptance, and Use of Technology) 2 by focusing on the findings and recommended future research. The papers, proceedings and dissertations included in the analysis were identified technology acceptance as the focus of their studies. This search was supplemented various websites which host scientific journals such as Emerald, Science Direct and Google Scholar. The initial search produced 65 papers. The studies examined works which employed UTAUT and UTAUT 2 by focusing on findings on the core constructs of UTAUT to predict Behavioral Intentions. The results confirmed previous studies that the four constructs of UTAUT contributed to Behavioral Intention even though PE seemed to be the most significant contributors. Findings also suggest UTAUT 2 has been more explanatory and list the suggestions for future works. The immediate implications are for researchers who wish to examine behavioral intentions, and managers who wish to ensure the acceptance and use of a new system or technology. This study bears a number of limitations. Number of papers examined is one of them. It would be more accurate to increase the number of paper examined. The other limitation is the ability to draw a statistical conclusion each research examined. This is due to a great variety of research topics, methods, constructs and contexts.